Mensuração das dimensões cardíacas pelo método VHS (Vertebral Heart Size) em cães - Inamassu, Letícia Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
It is imortant to be able to evaluate the cardiact size . In 1995, was proposed by Buchanan and Bücheler a new way to measure the dimensions of the cardiac silhouette. This study aims to gather several studies of the cardiac dimensions by VHS method in the right lateral recumbency of of different breeds of dogs in a single work, facilitating the assess to information. Deep chest breeds have a smaller mean VHS value than the barrel chest breeds, showing that there is a variation of the VHS values acoording to the thoracic conformation of each breed, which indicates that there is a need to recognize the specific VHS values according to the breed standard to not to interpret the cardiac measurement in a wrong way through not compatible reference values for the animal. There is the individual variation that should be taken into accont at the time of measurement. The VHS is a helper method to a radiographic evaluation of the heart, and the ultrasonography remains the gold standard for the evaluation of the cardiac chambers and other changes of the heart

É importante ser capaz de avaliar o tamanho cardíaco radiograficamente. Em 1995, foi proposta por Buchanan e Bücheler uma nova forma de se avaliar as dimensões da silhueta cardíaca. O presente estudo tem por objetivo reunir diversos estudos das dimensões cardíacas pelo método VHS em decúbito lateral direito de diferentes raças de cães em um único trabalho, facilitando o acesso às informações. Raças de tórax profundo apresentaram um valor médio de VHS menor que as raças de tórax em formato de barril, mostrando que há variação dos valores de VHS de acordo com a conformação torácica de cada raça, o que indica que existe a necessidade de se conhecer os valores específicos de VHS de acordo com o padrão racial para que não se interprete a mensuração cardíaca de forma errônea através de valores de referência não compatíveis com o animal. Existe a variação individual que também deve ser levada em consideração no momento da mensuração. O VHS é um método auxiliar para a avaliação radiográfica do coração, e a ultrassonografia continua sendo o padrão ouro para avaliação das câmaras cardíacas e outras alterações do coração
Keywords: Cão; Tórax – Radiografia; Dogs; Thoracic radiography; Racial variation